The earliest baleen whale from the Mediterranean: large‐scale implications of an early Miocene thalassotherian mysticete from Piedmont, Italy. (19th August 2020) - Bisconti, Michelangelo; Damarco, Piero; Mao, Selina; Pavia, Marco; Carnevale, Giorgio
Abstract: The discovery of an early Miocene chaeomysticete from the Pietra da Cantoni Group in Piedmont (north‐western Italy) allowed for the establishment of Atlanticetus lavei gen. et sp. nov. The new species is represented by a partial skeleton including the periotic and tympanic bullae and has an anatomical resemblance to Atlanticetus patulus (comb. nov.) from the western North Atlantic. The early Miocene age of the new specimen supports the view that it represents the oldest record of Chaeomysticeti from the Mediterranean. A new phylogenetic analysis showed that both A. patulus and A. lavei belong to a radiation of basal thalassotherian taxa. The basal thalassotherians are monophyletic to the exclusion of Cetotheriidae and Balaenopteroidea. The reconstruction of ancestral characters at selected nodes indicates that the group including Atlanticetus and living balaenopterid taxa independently evolved rostra wide at the base, an anterolateral expansion in the tympanic bulla, and a peculiar arrangement of the endocranial foramina of the periotic, exhibiting a noteworthy phenomenon of convergent evolution in feeding and hearing functions with Balaenopteridae. Palaeobiogeographical analysis shows that the North Pacific was the centre of origin of Balaenomorpha (crown mysticetes), Thalassotherii and Balaenoidea. The recurrent invasion of the Mediterranean by balaenomorph mysticetes occurred from both the North Atlantic and North Pacific.